A Comparative Study on Rollout of Quality Diagnostic Service at Subcenter Level in Implemented and Control Blocks of Balangir - Manasee Panda; Sushree Priyadarsini Satapathy; Tushar Kanti Meher; Anil Kumar Agrawal (Indian Journal of Public Health)
The quasi-experimental study was conducted to evaluate the benefit gained by the use of digital devices with the Sankalp app for detecting the high-risk pregnancy (HRP) cases during Village Health and Nutrition Day (VHND) sessions in the implemented blocks. Significantly more number of high-risk cases were detected in the experimental blocks (χ2 = 5.7075, at P < 0.01). In addition to it, the study revealed no follow-up of high-risk cases, no supervision, and lack of basic amenities, in the VHND sessions. Hence, strengthening and scale-up of the Sankalp app model for early identification, tracking, and management of HRPs were advocated.